KOPERASI SEKOLAH SEBAGAI BASIS PENGEMBANGAN MODEL PEMBELAJARAN KOPERASI DI SMA NEGERI KOTA SURAKARTA - Sari, Prajna Paramita; Santoso, Sigit; Murtini, Wiedy (Jurnal Pendidikan Insan Mandiri, 2016)
The purpose of this research is to produce a learning model based on cooperatives school in state senior hight school of Surakarta City. This study is the development of previous research by Borg and Gall. It passed 9 stages, include: (1) research and collecting information, (2) planning, (3) development of preliminary form of the product, (4) preliminary field testing, (5) main product revision, (6) main field testing, (7) operational product revision, (8) operational field testing and (9) final product revision. Validation of products involved experts, i.e. the materials experts, learning model experts and practitioners of cooperatives and economic subject teachers. The focused group discussionwas conducted by the Economics teachers who teach in tenth grade. Testing the cooperative learning model school-based cooperative was conducted on students of tenth grade in three schools, namely SMAN 6 SKA, SMAN 7SKA and SMAN 8 SKA. Results of the study are in form of: (1) The cooperative learning model which is needed in state senior high school in SurakartaCity, (2) design of school-based cooperative learning model, (3) the school-based cooperative learning model is valid, (4) the effectiveness of school-based cooperative learning model, and (5) learning model for cooperative learning development efforts in state senior high school of Surakarta.The results of this study include determining the cooperative learning model needed in state senior high school of Surakarta, producing a draft of school-based cooperative learning model, result a validschool-based cooperative learning model, determining the effectiveness of school-based learning model and resultingcooperative learning model for development efforts of cooperative learning in state senior high school of Surakarta. The use of school-based cooperative learning can improve students understanding about the cooperative and improve the students? awareness about the role of cooperatives and schoolcooperative. Key words: model of learning, development research, state senior high school of Surakarta.